Shear capacity of rc beams strengthened with externally bonded frp composite sheets - Kotula, Patrik; Zemko, Stefan (Communications - Scientific letters of the University of Zilina, 2004)
The strengthening of concrete structures using fibre reinforced polymer (FRP) materials has become a growing area in the construction industry over the last few years. Valuable research work is going on all over the world. This work is focused on theoretical, numerical and experimental analysis of the RC beam strengthened with a carbon fibre reinforced polymer (CFRP) sheet of the MBT-MBrace CF 640 type in a shear span of the RC beam. The aim of this paper is to present a simple design approach of calculation of a CFRP sheet contribution to the shear capacity of the RC beams and to compare results with values obtained from numerical analysis based on the finite element method (FEM) with ATENA-2D program being employed and with experimental results. The experiment confirms availability of CFRP sheets for shear strengthening of RC beams.